Age and driving mechanisms of the Eocene–Oligocene transition from astronomical tuning of a lacustrine record (Rennes Basin, France) - S. Boulila; S. Boulila; G. Dupont-Nivet; G. Dupont-Nivet; B. Galbrun; H. Bauer; J.-J. Châteauneuf (Climate of the Past, 2021)
The Eocene–Oligocene Transition (EOT) marks the onset of the Antarctic glaciation and the switch from greenhouse to icehouse climates. However, the driving mechanisms and the precise timing of the EOT remain controversial mostly due to the lack of well-dated stratigraphic records, especially in continental environments. Here we present a cyclo-magnetostratigraphic and sedimentological study of a ∼ 7.6 Myr long lacustrine record spanning the late Eocene to the earliest Oligocene, from a drill core in the Rennes Basin (France). Cyclostratigraphic analysis of natural gamma radiation (NGR) log data yields duration estimates of Chrons C12r through C16n.1n, providing additional constraints on the Eocene timescale. Correlations between the orbital eccentricity curve and the 405 kyr tuned NGR time series indicate that 33.71 and 34.10 Ma are the most likely proposed ages of the EO boundary. Additionally, the 405 kyr tuning calibrates the most pronounced NGR cyclicity to a period of ∼1 Myr, matching the g1–g5 eccentricity term, supporting its significant expression in continental depositional environments, and hypothesizing that the paleolake level may have behaved as a low-pass filter for orbital forcing. Two prominent changes in the sedimentary facies were detected across the EOT, which are temporally equivalent to the two main climatic steps, EOT-1 and Oi-1. We suggest that these two facies changes reflect the two major Antarctic cooling/glacial phases via the hydrological cycle, as significant shifts to drier and cooler climate conditions. Finally, the interval spanning the EOT precursor glacial event through EOT-1 is remarkably dominated by obliquity. This suggests preconditioning of the major Antarctic glaciation, either from obliquity directly affecting the formation/(in)stability of the incipient Antarctic Ice Sheet (AIS), or through obliquity modulation of the North Atlantic Deep Water production.